2009
DOI: 10.1016/j.rmed.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutathione-S-transferase polymorphisms on clinical outcome of ALI/ARDS patient treated with N-acetylcysteine

Abstract: Oxidative stress has a proven role in pathophysiology of acute respiratory distress syndrome. The antioxidant drugs, especially N-acetylcysteine (NAC) have been used for years to overcome oxidative stress effects in patients. In the present study we have investigated the effects of NAC treatment (IV NAC in 150mg/kg at the first day followed by 50mg/kg/day for three days) on 27 ICU patients with ALI/ARDS considering the glutathione-S-transferase genetic variations, as an important enzyme contributing in oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 44 publications
1
95
0
7
Order By: Relevance
“…Randomized, double-blind, placebo-controlled studies concluded that intravenous administration of N-acetyl-cysteine in patients with ARDS reduced the need for ventilatory support and improved systemic oxygenation, but failed to reduce mortality (9,11). More recent studies using higher concentrations of N-acetyl-cysteine in patients with ALI reported that reduction of mortality depended on polymorphisms in the glutathione-S-transferase gene (45). Thus, beneficial effects of N-acetyl-cysteine in human ARDS remain in dispute.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized, double-blind, placebo-controlled studies concluded that intravenous administration of N-acetyl-cysteine in patients with ARDS reduced the need for ventilatory support and improved systemic oxygenation, but failed to reduce mortality (9,11). More recent studies using higher concentrations of N-acetyl-cysteine in patients with ALI reported that reduction of mortality depended on polymorphisms in the glutathione-S-transferase gene (45). Thus, beneficial effects of N-acetyl-cysteine in human ARDS remain in dispute.…”
Section: Discussionmentioning
confidence: 99%
“…For example, selection of patients based on haptoglobin genotype in diabetic patients treated with vitamin E [239] or glutathione-S-transferase genotype in acute respiratory distress syndrome (ARDS)/acute lung injury patients treated with N-acetylcysteine [240], or apo genotype in over-weight individuals treated with quercetin as a blood pressure-lowering agent [144] could alter the response to antioxidant therapy. The real challenge in this regard, is to establish patient selection methods that can predict who is more likely to benefit from antioxidant therapy [241].…”
Section: C-patients Do Not Equally Benefit From Antioxidant Therapymentioning
confidence: 99%
“…For instance, individuals with homozygous GSTM1 gene deletions appear to be more susceptible to DNA damage induced by GSTM1 substrates (32) and are more at risk of developing lung adenocarcinoma (7). Preliminary clinical studies also suggest that attenuated GST expression may contribute to ALI (25). Moradi and colleagues (25) showed that GSTM1 polymorphisms were associated with increased mortality in critically ill patients with ALI/ARDS.…”
mentioning
confidence: 99%